The Kentucky encyclopedia - Kleber, John E., 1941-; Wymer, Scott A.; Kmetz, Thomas P. (University Press of Kentucky, 1992)
The Kentucky Encyclopedia's 2,000-plus entries are the work of more than five hundred writers. Their subjects reflect all areas of the commonwealth and span the time from prehistoric settlement to today's headlines, recording Kentuckians' achievements in art, architecture, business, education, politics, religion, science, and sports. Biographical sketches portray all of Kentucky's governors and U.S. senators, as well as note congressmen and state and local politicians. Kentucky's impact on the national scene is registered in the lives of such figures as Carry Nation, Henry Clay, Louis Brandei.